2023
DOI: 10.1007/s12265-023-10448-9
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmented QRS Complex in Lead V1: Time for an Update of the Athlete’s ECG?

Marco Vecchiato,
Giulia Quinto,
Nicola Borasio
et al.

Abstract: Differentiating between ECG patterns related to athletes' heart remodeling and pathological findings is a challenge in sports cardiology. As the significance of fragmented complex in athletes remains uncertain, this study aimed to assess the presence of fragmented QRS in lead V1 (fQRSV1) among young athletes and its association with heart adaptations and arrhythmias. Young athletes referred for annual pre-participation screening receiving a maximal exercise testing and transthoracic echocardiography from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…These findings may reflect the fact that a dilated RV outflow tract could be associated with a greater angulation of the RV myocardial band at the transition site from the RV free wall to pulmonary conus, leading to a more sudden change in the direction of RV electrical activation in the RV outflow tract [30]. Although two previous studies have reported increased prevalence of QRS fragmentation in V1 among athletes and its association with indexes of RV dimensions, the QRS fragmentation was defined in a restrictive way as the presence of quadriphasic QRS complex without including cases with notched QRS in V1 [11,12]. Moreover, the disappearance of QRS fragmentation in V1 after deep inspiration in the healthy nonathletes of the current study could be explained by the inspiration-induced clockwise rotation of the heart minimizing the view of the RV outflow track by V1 [33].…”
Section: Qrs Fragmentation In Athletesmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may reflect the fact that a dilated RV outflow tract could be associated with a greater angulation of the RV myocardial band at the transition site from the RV free wall to pulmonary conus, leading to a more sudden change in the direction of RV electrical activation in the RV outflow tract [30]. Although two previous studies have reported increased prevalence of QRS fragmentation in V1 among athletes and its association with indexes of RV dimensions, the QRS fragmentation was defined in a restrictive way as the presence of quadriphasic QRS complex without including cases with notched QRS in V1 [11,12]. Moreover, the disappearance of QRS fragmentation in V1 after deep inspiration in the healthy nonathletes of the current study could be explained by the inspiration-induced clockwise rotation of the heart minimizing the view of the RV outflow track by V1 [33].…”
Section: Qrs Fragmentation In Athletesmentioning
confidence: 99%
“…Thirdly, the current study assessed QRS fragmentation in each specific lead and not only in groups of contiguous leads. Furthermore, we defined the QRS fragmentation in V1 broadly, including all the subcategories of QRS fragmentation, as opposed to the restrictive definition of previous studies investigating only the presence of quadriphasic QRS complex without including cases with notched QRS in V1 [11,12]. Finally, the present study investigated QRS fragmentation in individuals with a wide age range, including not only children and adolescents but also elderly individuals.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation